DAMPAK BEBERAPA FAKTOR TERHADAP KEAHLIAN AUDIT (AN EMPIRIC STUDY AT REGISTERED PUBLIC ACCOUNTING OFFICER IN SURABAYA) - Sri Hastuti (The Indonesian Accounting Review, 2012)
Public accounting profession developed a long with the difference of importance of internalinformation user and external information user. The company’s management needs service ofthe third people that is Independent Auditor in other that responsibility to the external partycan be trusted, where as the company external party needs service at the third party to getbelieve that the income statement which served by company management can be trust as thebasic of decisions interpretation which is taken by them. Belong to the position, so the auditoris demanded to be able to maintain the belief from client and the others audited IncomeStatement’s users. This belief must be always improve and supported by the audit’s competence.Audit’s competence which is had by the auditor is related with the knowledge he had,the knowledge can be got from the formal education and enhanced thought exercising andexperiences in audit practice. Based on the background, the goal of this research is to determinethat education, experience, and practicing of public accounting influenced toward theaudit’s competence. The determining of sample in this research is using simple random samplingtechnical. The number of sample which is used in this research is 40 public accountingwho work at Registered Public Accounting Officer in Surabaya. The source of data which isgot from the questioner spread and then analyzed using double linier regression and examinedusing F test and t test. Based on the double linier regression analysis, it can be concludedthat education, experience and practicing of public accounting are influenced towardthe audit’s competence stimulatingly. Where as partially only the education of public accountingwhich is influence toward to audit’s competence.